Model Pembelajaran STAD Berbantuan Media Scrapbook Untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Vita Apriliya; Mohammad Kanzunnudin; Imaniar Purbasari (EduBasic Journal: Jurnal Pendidikan Dasar, 2020)
This study aimed to improve students’ learning outcomes through the STAD model aided by Scrapbook media in theme 7 "The Beauty of Diversity in My Country" in the content of Indonesian Language and Social Sciences subject of fourth grade of elementary school. The method used in this study was classroom action research conducted in fourth grade of elementary school, which numbered 19 students. This research was conducted in two cycles, each cycle consisting of four stages, namely planning, implementation, observation and reflection. Data collection was obtained through tests, observations, interviews and documentation. The results showed that an increase in students’ learning outcomes in the cognitive aspect of cycle I gained a classical completeness of 63.16%, then an increase in cycle II gained a classical completeness of 78.95% in Indonesian Languange Subject.  In the Social Science subject,  cycle I received a classical completeness of 52.63% and increased in cycle II gained 73.69% classical completeness. Psychomotor domain of students’ learning outcomes also experienced an increase when Indonesian Language cycle I gained an average of 72.28% and increased in cycle II by 77.31% with good criteria. In the Social Science, cycle I obtained an average of 72.63% and increased in the cycle II by an average of 80.94% with good criteria. It can be concluded that the application of the STAD learning model assisted by Scrapbook media can improve student learning outcomes in the cognitive and psychomotor domains.